Influence of hydrodynamic patterns on foraminifera in reef sediment sat the Praia do Forte beach and Itacimirim, Bahia, Brazil - Moraes, Simone Souza de; Machado, Altair de Jesus (Anuário do Instituto de Geociências, 2006)
Abstract